Peranan Penyuluh Pertanian Lapang dan Partisipasi Petani dalam Keberhasilan Program Upsus Pajale di Kecamatan Natar, Kabupaten Lampung Selatan: Role of Agricultural Extension Worker and Participation of Farmers on Success of Upsus Pajale Program in Natar District, South Lampung Regency - Adhanta Reksa Darma; Tubagus Hasanuddin; Rio Tedi Prayitno (Research and Social Study Institute (RESSI), 2022)
The purpose of this research was to determine the implementation of the Program, to determine the role of PPL in the Program, to determine the participation of farmers in the Program, and to determine the relationship of the role of the field agriculture instructor and farmer participation to the success of the Program. The determination of the location of the research was carried out deliberately in Natar District, South Lampung Regency. Respondents in this research were 51 farmers. This research was conducted in September-Oktober 2019. This research used a survey method and using descriptive analysis and usedRank Spearman correlation test. The role of field agriculture instructors in the program which consists of seven indicators is classified as high. Farmer participation in the Program is included in the high category, which means that farmer participation is very instrumental in the program. In the rice commodity, there is a relationship between the role of the field agriculture instructor with the success of the program and there is a relationship with the farmers participation with the success of the program, whereas in the case of corn, there is an unreal relationship between the role of the field agricultural extension agent and the success of the program. unreal relationship between farmer participation and the success of the program.